T Cell Hierarchy in the Pathogenesis of Psoriasis and Associated Cardiovascular Comorbidities - Casciano, Fabio; Pigatto, Paolo D.; Secchiero, Paola; Gambari, Roberto; Reali, Eva (Frontiers in Immunology, 2018)
The key role of T cells in the pathogenesis of cutaneous psoriasis has been well described in the last decade and the knowledge of the relative role of the different subsets of T cells in psoriasis pathogenesis has considerably evolved. Now it is clear that IL-17A producing T cells, including Th17/Tc17, have a central role in the pathogenesis of cutaneous psoriasis and therapies blocking the IL-17A pathway show high clinical efficacy. By contrast, the contribution of IFNγ-producing T cells has progressively become less clear because of the lack of efficacy of anti-IFNγ antibodies in clinical studies. In parallel, the role of CD8+ T cells specific for self-antigens has been revived and increasing evidence now indicates that in psoriatic skin the majority CD8+ T cells are present in the form of epidermal tissue resident memory T cells. In the last years it also emerged the possibility of a contribution of T cell recirculation in the pathogenesis of psoriasis and its systemic manifestations. The aim of this review is to define a hierarchy for the different subsets of T cells in the T-cell mediated inflammatory cascade in psoriatic skin. This analysis will possibly help to distinguish the subsets that initiate the disease, those involved in the establishment of the self-sustaining amplification loop that leads to the cutaneous clinical manifestations and finally the subsets that act as downstream players in established lesions. Specific T cell subpopulations finally will be considered for their possible role in propagating inflammation at distant sites and for representing a link with systemic inflammation and cardiovascular comorbidities.